New knowledge for omarigliptin tablets: dissolution assay -behavior in different media and biopharmaceutical classification - Emanuelli, Juliana; Volpato, Nadia Maria; Scherman Schapoval, Elfrides Eva (Drug Analytical Research, 2026)
Omarigliptin (OMG) is an active substance for the treatment of type 2 diabetes and it is representing of the dipeptidyl peptidase IV inhibitors class, an important enzyme in the regulation of blood glucose. It was launched on the Japanese market in 2015 as a weekly dose innovation. This work aimed to report the results obtained of the OMG tablets solubilization in different media, evaluate the dissolution profiles in the chosen media, propose the biopharmaceutical classification, in addition to validate the dissolution method. After solubility test, the dissolution assay was conducted and a rapid process of tablets disintegration and dissolution was observed in three media having different pH values, they were acid hydrochloric 0.01M at pH 3.1, sodium acetate buffer at pH 4.5 and potassium phosphate buffer at pH 6.8. The potassium phosphate buffer medium was chosen to proceed with the dissolution method validation. With the profiles obtained in the three tested media it was possible to conclude that the dissolution is very fast, with 100% of the active substance dissolved in less than 10 min for all tested media. In addition, with the evaluation of the dissolution profile obtained in this work and data available in the literature, it was possible to suggest that OMG belongs to class I of the biopharmaceutical classification system. The proposed method was validated and contained all the necessary parameters recommended by the official guides.